Water-based mud formulations in drilling Terengganu shale formation - Ismail, Abdul Razak; Lim, Felix Choong Hooi (1995)
Water-based muds are used in drilling operation due to its environmental friendly nature. However, water-based mud systems are usually associated with shale problems that can cause shale hydration, swelling, dispersion and abnormal pressure thus causing drilling problems like washout, stuck pipe and hole enlargement. The purpose of this study is to formulate water-based muds that can minimize shale problems while drilling offshore Terengganu fields. Terengganu shale (also called K shale) is basically sedimentary rocks that have been laid down over geologic time in marine basins. They composed of quartz, feldspar, calcite and other clay fractions like kaolinite, illite and inter layered varieties in different proportions. Terengganu shale is used in this study to determine the classifications of its shale. A series of x-ray diffraction, capillary suction test and shale inhibition rate test was carried out to determine the mineralogy and dispersive/brittle attributes of the Terengganu shale. The best suited mud system to drill Terengganu shale will be proposed.